Cultural Value and Locality in the Merapi Daily Short Story Collection “Lintang Johar Cikal Bakal Mataram Islam” - Agung Tri Laksono; Else Liliani (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2023)
Cultural Values And Locality In The Collection Of Daily Merapi Short Stories “Lintang Johar Cikal Bakal Mataram Islam” By Iis Suwartini. The presence of literary works is closely related to the culture that exists in society. Literary works exist as a means to invite people to live in tune with the existing culture. In line with this, this study aims to determine the values of Javanese culture and locality contained in the Kumoulan Kompas Daily Short Story "Lintang Johar Cikal Bakal Mataram Islam" by iis Suwartini. This research is descriptive qualitative research. The main data source which is the object of study in this research is the Kompas Daily Short Story Collection published in 2021 by Iis Suwartini. Retrieval of research data is done through heuristic reading techniques. The interactive data analysis technique from Miles & Huberman is a data analysis technique which includes techniques of: (1) collecting data, (2) reducing data, (3) presenting data, and (4) drawing conclusions. This research produces written data. The results of the study show that the cultural values contained in a collection of short stories are 1) the nature of human life, 2) the nature of human work, 3) the nature of human position in space and time, 4) the nature of the relationship between humans and nature, and 5) the nature of the relationship between humans. The locality that appears is the locality of Java, which has been successfully identified through the characters, plot, setting, style of language and story title. Overall, this research is expected to be a basis for bringing up relevant research related to cultural values and locality in literary works.